Filial Ties: Godwin's Deloraine and Mary Shelley's Writings - Chatterjee, Ranita (European romantic review, 2007)
In this essay, I argue that through a reading of William Godwin's last novel Deloraine and Mary Shelley's Mathilda, "The Mourner," and Falkner, one can begin to trace the aesthetics of a Romantic collaboration that explores the dynamics of father-daughter relationships. From Godwin's Mary Fleetwood and Shelley's Mathilda and Clarice/Ellen in "The Mourner" to Godwin's Margaret Borradale and Catherine in Deloraine and Shelley's Elizabeth Raby in Falkner, there is an evolution of the portrayal of the daughter in strikingly similar characters. These narrative repetitions and distortions are simultaneously discursive, because they occur between and among liberal texts, and libidinal, since they emerge out of the father-daughter (literary) relationship. I also argue that the signifiers "William Godwin" and "Mary Shelley" are partial Kristevan subjects who are intimately invested in each other and, more importantly, only emerge as Foucauldian author-functions as effects of the writings that they produce intertextually. As I discuss, Deloraine becomes a key text for understanding the Godwin-Shelley literary exploration of the dynamics of father-daughter relationships.